Pengaruh Profitabilitas (ROA), (ROE), dan Leverage (DER) terhadap Harga Saham Perusahaan Pertambangan yang Terdaftar di BEI 2019-2023 - Aditya Yunanto; Atri Nodi Maiza Putra (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the effect of profitability ratios (Return On Assets/ROA, Return On Equity/ROE) and leverage ratio (Debt to Equity Ratio/DER) on stock prices of mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The study is motivated by stock market uncertainty influenced by companies’ financial performance. This research employs a quantitative approach with a sample of 14 companies selected through purposive sampling. Secondary data were analyzed using regression to examine the relationship between these variables and stock prices. The results show that, partially, ROA, ROE, and DER have no significant effect on stock prices. However, simultaneously, these variables influence stock prices. These findings suggest that companies should improve asset and equity management efficiency to enhance sustainable profitability. Additionally, companies must optimize capital structure to maintain leverage at an ideal level and minimize financial risk. Future research is recommended to expand the sample, extend the analysis period, and consider macroeconomic factors, market sentiment, and government policies that may affect stock prices.